Smart Residential Multi Level Plantation System - Pranay Singh Parihar, Karrmanya Pande, Patri Sanjana, Titirsha Sarkar; Kanimozhi G (International Journal of Advanced Science and Technology, 2020)
The demand to supply ratio for plants such as basic vegetables or horticultural plants is often very high on the market, meaning demand is not met .This leads towards an unwanted burden on the market and a substantial rise in price. This resulted in developing a multi-level residential planting system. As the name suggests, the system will be built for residential purposes, mainly for growing plants (agricultural or horticultural) at home without any unnecessary burden on the user. This system will ensure an optimum, natural, and rapid rate of growth for various plants. This is achieved by tenaciously monitoring and controlling environmental factors using IoT devices. This control allows the plants to draw the essential nutrients as much as it can from the environment and provide the remaining by stimulating the environment. The prototype developed is controlling two factors i.e. light and water. Other factors like temperature can be seen on a display device and can be monitored. The multi-level system also inculcates the idea to optimize space so that more plants can be grown in less space in a user- friendly manner. With the help of this system a person can grow natural plants with ease and can in turn help in reducing the demand to supply ratio. The simulation and the prototype implementation prove that the user will invest minimum time in the process and will eliminate the tedious efforts to grow a plant and meet the demand.